Transcriptional Regulation of T-Cell Lipid Metabolism: Implications for Plasma Membrane Lipid Rafts and T-Cell Function - Robinson, George A.; Waddington, Kirsty E.; Pineda-Torra, Ines; Jury, Elizabeth C. (Frontiers in Immunology, 2017)
It is well established that cholesterol and glycosphingolipids are enriched in the plasma membrane (PM) and form signalling platforms called lipid rafts, essential for T-cell activation and function. Moreover, changes in PM lipid composition affect the biophysical properties of lipid rafts and have a role in defining functional T-cell phenotypes. Here we review the role of transcriptional regulators of lipid metabolism including liver X receptors α/β (LXR/LXRβ), peroxisome proliferator-activated receptor γ (PPAR-γ), estrogen receptors α/β (ERα/β) and sterol regulatory element-binding proteins (SREBPs) in T-cells. These receptors lie at the interface between lipid metabolism and immune cell function and are endogenously activated by lipids and/or hormones. Importantly, they regulate cellular cholesterol, fatty acid, glycosphingolipid and phospholipid levels but are also known to modulate a broad spectrum of immune responses. The current evidence supporting a role for lipid metabolism pathways in controlling immune cell activation by influencing PM lipid raft composition in health and disease, and the potential for targeting lipid biosynthesis pathways to control unwanted T-cell activation in autoimmunity is reviewed.